Axicon lenses with chiral-focusing properties modeling by means of analytical functions. (April 2023) - Moreno, Enrique; Colombier, Jean-Philippe
Highlights: Generation of analytical functions for axicon lens construction and simulation. Non-linear full-wave simulation in finite differences in the time domain of analytically defined lenses. Numerical verification of conservation relations in electromagnetic structures produced by the study/generated lenses. Potential for future studies of vortical properties of asymmetric pulsed electromagnetic structures. Abstract: Axicon lenses exhibit a large focal depth that generates an energy distribution, resulting in non-diffracting beams' generation. These light structures are called Bessel beams and show numerous important applications in optical signal processing, imaging, transparent material processing, and even in metal drilling/cutting manufacturers. Asymmetrical and twisted axicon-lenses are boundary conditions on the Maxwell equation able to generate complex-structured light fields with specially designed intensity, phase, and polarization distributions. This paper presents a set of analytical functions that allows the definition of such surfaces with absolute freedom in relation to the lens profile. Obviously, before manufacturing any lens, it is necessary to compute its electromagnetic output in order to save resources. In this sense, we have studied some of these lenses by simulation using the well-known finite difference method in the time domain. Some necessary verification related to conservative magnitudes, such as the Poynting vector, have been done analytically and numerically. The numerical results show the distribution of iso-values corresponding to the electric field and 3D-vectorial representation of the chirality flux and the Poynting vector. Finally, by means of discrete fast Fourier transform, it is shown the field distributions as well as the power before and after the lens per frequency.